Synergist upper-limb resistance training reduces blood pressure in young normotensive men: a piloty study - Moura, Eliézer Guimarães; Marlindo Santana Nunes, Wilton; Oenning Col, Luan; Antunes-Correa, Ligia; Moreno Jr, Heitor; Rodrigues, Bruno (Journal of Interdisciplinary Lifestyle Studies, 2024)
Purpose: We aimed to verify the effects of 8 weeks of resistance training on the synergistic and non-synergistic routines on peripheral and central blood pressure, biochemical variables, and pulse wave behavior recreationally trained men. Methods: A program of resistance training predominantly for the upper limbs was prescribed. Ten healthy young men participated in a routine synergistic, and 12 men performed a routine non-synergistic. Peripheral and central arterial pressures (oscillometric and applanation tonometry methods, respectively), as well as biochemical variables (lipid profile, glucose, hemoglobin, and noradrenaline) and arterial stiffness (pulse wave velocity by applanation tonometry), were evaluated. Results: No differences between group were observed in biochemical variables, except a decrease in values of the hemoglobin concentration at the post compared to pre-condition in the non-synergistic group (p= 0.015). No differences between group were observed for tonometry applanation variables. However, an increase in peripheral and central diastolic blood pressures was detected in the non-synergistic group (p= 0.026 and 0.021, respectively). In the synergistic group, a reduction in diastolic blood (p= 0.041) and increased central pulse pressure (p= 0.046) were observed. Conclusions: Thus, the resistance training performed predominantly with the upper limbs does not increase arterial stiffness but may increase diastolic blood pressures in healthy young men.